Mite diversity (Acari: Tetranychidae, Tydeidae, Iolinidae, Phytoseiidae) and within-tree distribution in citrus orchards in southern Spain, with special reference to Eutetranychus orientalis - Vela-López, José M.; Wong, Eva; Jaques, Josep A.; Ledesma, Claudio; Boyero, Juan R. (2018)
Mite diversity of selected citrus orchards in Andalusia (southern Spain) was studied during 2002-2007. The following species were found: Eutetranychus orientalis, Tetranychus urticae, Panonychus citri (Tetranychidae), Tydeus californicus, Lorryia formosa (Tydeidae), Pronematus ubiquitus (Iolinidae), Euseius stipulatus, Typhlodromus phialatus, Neoseiulus californicus, Euseius scutalis, Phytoseiulus persimilis, Paraseiulus talbii and Neoseiulus cucumeris (Phytoseiidae). Eutetranychus orientalis was the dominant tetranychid species in orange and lemon trees, whereas T. urticae was slightly more abundant in mandarines. The most abundant tydeid in clementine and orange was Tydeus californicus, in lemon it was L. formosa. The iolinid P. ubiquitus was found in very low numbers. With respect to phytoseiids, E. stipulatus was dominant in the three citrus species. Eutetranychus orientalis had a unimodal phenology, peaking only in autumn, whereas the other two tetranychids had two maxima. Tydeus californicus showed one or two peaks depending upon the citrus species, and E. stipulatus also had two peaks, one in spring and one in autumn. The mites displayed a non-random distribution in the tree. Eutetranychus orientalis preferred the outer and upper leaves. On the contrary, tydeids (mainly T. californicus) and phytoseiids (mainly E. stipulatus) preferred inner and lower leaves. These preferences had not been sufficiently described previously, and they are important for sampling plans.